Dynamics of Social Anxiety Among First-Year Students: Gender and Age Perspectives - Wijayanti, Lanny Ilyas; Sanyata, Sigit (Universitas Negeri Padang, 2024)
This study explores the dynamics of social anxiety among first-year university students, focusing on the challenges they face and the adaptations they employ. The primary objective is to understand how specific factors influence students' anxiety levels, particularly examining the correlations between gender, age, and facets of social anxiety. Employing a survey design, data were collected using a validated questionnaire comprising 32 items that measure key aspects of social anxiety: Fear of Negative Evaluation, Avoidance of Social Situations with Strangers, and General Avoidance of Social Situations. The study analyzed responses from 334 students, predominantly female (69.2%) and under 20 years of age (84.4%), with most participants enrolled in the Faculty of Education and Psychology (67.1%). Results indicate significant correlations between the examined factors and social anxiety levels, with p-values < 0.05 across all aspects. Gender was significantly associated with general anxiety, with females exhibiting higher anxiety levels. Age was strongly correlated with Fear of Negative Evaluation, while faculty affiliation showed a significant relationship with Fear of Negative Evaluation and General Avoidance of Social Situations, but not with overall anxiety levels. These findings highlight the critical role of gender in influencing social anxiety, while the effects of age and faculty vary across specific dimensions of anxiety.